A tale Magnolious - Nelson, Suzanne, 1976- (Alfred A. Knopf, an imprint of Random House Children's Books, 2019)
With a touch of magic and a harvest of hope, a young orphan and her exceptional elephant set out to change the destiny of a dying town, devastated by a decade of dust storms, proving that from the smallest seeds, grow the greatest friendships.